Relationships between Law Enforcement Authorities and Drone Journalists in Spain - Gallardo-Camacho, Jorge (2020)
The article analyzes the relationship between law enforcement authorities and drone journalists, professionals who use unmanned aerial vehicles (UAVs) for newsgathering purposes, in Spain. The study has two specific objectives. First, to identify the criteria that law enforcement authorities have set for the public dissemination in traditional and social media of the drone footage they have obtained as part of their police operations, and to characterize the relationship that exists between law enforcement authorities and drone journalists. The study is guided by three hypotheses: Spanish law enforcement authorities have more capacity than journalists to shoot aerial news footage (H1); for Spanish law enforcement authorities, the informational use that can be made of the drone footage they obtain is of secondary importance (H2); and drone journalists feel their work is heavily restricted by law enforcement authorities (H3). These hypotheses are tested with the use of in-depth interviews with representatives of three law enforcement organizations in Spain and five drone pilots who have collaborated with news media outlets. The study concludes that the current regulatory framework for UAVs in Spain is very restrictive, in comparison to other countries, which prevents the development of drone journalism.